(untitled) (Research Nepal Journal of Development Studies, 2018)
There has often been a gap between policy intentions and outcomes in the field of local governance and public service delivery. Analyzing the factors for these discrepancies requires multi-level approaches that relate policy decisions formulated at the national and international level with the decisions of local governance stakeholders. An Institutional Analysis and Development framework is necessary ability to link multiple local governance levels. Yet most common literatures have been limited to the study of collective action among local communities without considering higher institutional and government levels. To overcome this limitation, I set the methodology of the framework, which bridges the gap between institutional, historical analysis, power-centers, and discourse analysis. This article aims at examining current public service delivery status, analyzing challenges of public service delivery of local government and assessing people’s experience of public service delivery of local government. In conclusion, current status of Local Government is illegal, incomplete and dysfunctional as it is in its service delivery. The major challenge is political instability and political reluctances for local election. The people’s experience over the public service is below the satisfactory level. Research Nepal Journal of Development Studies Vol.1(1) 2018 83-92